Case report: Successful immunomodulators combined with electromagnetic field therapy in a patient with methazolamide-induced Steven Johnson syndrome/toxic epidermal necrolysis overlap - Zhang, Naiju; Su, Tianjiao; Yan, Jingwen; Zhang, Mei; Zhao, Shousong; Liu, Chuanmiao; Chen, Tianping (Frontiers in Medicine, 2023)
Methazolamide is used to treat patients with glaucoma. However, as a sulfonamide derivative, methazolamide shares the same adverse reaction profile as other sulfa-based medications. Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare delayed-type hypersensitivity cutaneous reactions with high morbidity and mortality. Here, we report a severe SJS/TEN overlap syndrome in an 85-year-old Chinese male patient who received methazolamide 25 mg twice daily for his left eye glaucoma. The causal relationship between SJS/TEN and methazolamide was categorized as “highly likely” on the algorithm for assessing drug causality for epidermal necrolysis. In addition to the treatments with methylprednisolone and immunoglobulin, we used a special electromagnetic spectrum therapeutic apparatus to provide skin wound care. The patient had a thoroughly satisfying recovery. This is the first case report to use electromagnetic field therapy in a patient with SJS/TEN. We share our experience here and suggest that electromagnetic field therapy can provide advanced skin wound care and facilitate the recovery of SJS/TEN.